Morbidity and mortality profile of neonates admitted in a special care newborn unit of a tertiary care teaching hospital of Assam, India - Kutubur Rahman; Rukeya Begum (Barpeta Obstetrics and Gynaecological Society, 2020)
Objectives: The objective of study is to estimate the morbidity and mortality of newborns admitted at Special Care Newborn Unit (SCNU) of tertiary care hospital. Materials and methods: This hospital based retrospective study was carried out in SCNU, department of pediatrics, over a period of 4 years from 1st January 2016 to 31st December 2019. All newborns (0- 28 days) admitted into the SCNU during the study period were included in the study. Data were collected from the monthly reporting format and patient case records. Then they were compiled in MS excel and analyzed using appropriate statistical tools. Results: During this period of 4 years total 5649 number of patients were admitted in SCNU, inborn 3657 (64.7%) and out born 1992 (35.2%). 58.7% of babies were male. Almost equal number of normal weight (50.2%) and low birth weight babies (49.7%) were admitted. Similarly equal number of term (49.4%) and preterm babies (50.5%) were admitted. Birth asphyxia, babies with birth weight below 1800gm requiring special care, neonatal sepsis and jaundice requiring phototherapy were common morbidities requiring admission. Mortality was 11.4% which is higher in out born (14.3%) than inborn (9.9%). Birth asphyxia (53.9%) is the commonest cause of mortality followed by respiratory distress syndrome (RDS) with prematurity (23.2%) and neonatal sepsis (12.4%). Sepsis is higher in out born unit (18.5%) than inborn (7.7%). Highest number of death occurs in early neonatal period (88.5%) and among low birth weight baby (58.7%). First 72 hours of admission is crucial for survival as 78.2 % babies die during this period. Conclusion: Birth asphyxia, RDS with prematurity and neonatal sepsis are common cause of mortality. It is largely preventable by comprehensive antenatal, natal, neonatal care and health awareness among patients and society.